2014
DOI: 10.1021/es405585b
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Retention and Remobilization along Hydrological Pathways in Karst Terrain

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Karst landscapes are often perceived as highly vulnerable to agricultural phosphorus (P) loss, via 14 solution-enlarged conduits that bypass P retention processes. Although attenuation of P 15 concentrations has been widely reported within karst drainage, the extent to which this results from 16 hydrological dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 45 publications
2
49
1
1
Order By: Relevance
“…Previous studies indicated that 1-38 % of NAPI was exported by rivers (David and Gentry 2000;BorborCordova et al 2006;Russell et al 2008;Han et al 2011a, b;Sobota et al 2011), implying that the majority of NAPI was retained in soils, surface water sediments, and biomass Jarvie et al 2014), or even groundwater (Holman et al 2008;Roy and Bickerton 2014). This accumulated P, referred to as legacy P (i.e., surplus P stored in watershed landscapes that is derived from anthropogenic P inputs in previous years), is not addressed in the NAPI estimation, as well as the majority of current watershed models (Kleinman et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies indicated that 1-38 % of NAPI was exported by rivers (David and Gentry 2000;BorborCordova et al 2006;Russell et al 2008;Han et al 2011a, b;Sobota et al 2011), implying that the majority of NAPI was retained in soils, surface water sediments, and biomass Jarvie et al 2014), or even groundwater (Holman et al 2008;Roy and Bickerton 2014). This accumulated P, referred to as legacy P (i.e., surplus P stored in watershed landscapes that is derived from anthropogenic P inputs in previous years), is not addressed in the NAPI estimation, as well as the majority of current watershed models (Kleinman et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 96%
“…The contribution of legacy P has been recognized as a major cause for failure to achieve water quality targets 20-30 years after implementing nutrient management measures for the Chesapeake Bay watershed, Mississippi River basin, Florida's inland and coastal waters, and Lake Erie basin (Meals et al 2010;Kleinman et al 2011;Jarvie et al 2013;Sharpley et al 2013;Condron et al 2013;Haygarth et al 2014). Legacy P release and delivery to rivers is highly dependent on landscape P saturation (Kleinman et al 2011;Jarvie et al 2014), hydrological connectivity (Gentry et al 2007;Han et al 2011a), and storm runoff/erosion (Borbor-Cordova et al 2006;Hong et al 2012). Therefore, from the perspective of changes in climate and land management, legacy P release may be enhanced and subsequently has the potential to make a considerable contribution to the riverine P flux.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In order to judge whether the soil acts as a source or sink of P for the surface water (Pan et al, 2002), defined a criterion of = C/EPC 0 , and Jarvie defined EPC sat = ((EPC 0 − DIP)/EPC 0 ) × 100%, DIP (dissolved inorganic phosphate) (Jarvie et al, 2014). However, EPC 0 is in the denominator in both equations, both of the methods could easily enlarge the measurement error especially when EPC 0 is low.…”
Section: Phosphate Sorption Isotherm Experimentsmentioning
confidence: 99%
“…However, much of the topography in northwest Arkansas is karstic [3] [4]. Consequently, groundwater resources are susceptible to pollution from sources such as fertilizers and OWTSs [5]. Therefore, it is important to study OWTS function and limitations within the local region in order to better understand various system types to prevent environmental contamination and human health risks.…”
Section: Introductionmentioning
confidence: 99%
“…Water in the perched water table could also move horizontally throughout the soil, exiting as springs, which could ultimately flow into larger streams, rivers, and lakes or reservoirs [12]. Consequently, contaminants present in the perched water table could also rise to the surface becoming point or non-point source pollution [5] [13].…”
Section: Introductionmentioning
confidence: 99%